Critical review of micro-extraction techniques used in the determination of polycyclic aromatic hydrocarbons in biological, environmental and food samples. Issue 6 (2nd June 2020) - Jinadasa, B. K. K. K.; Monteau, Fabrice; Morais, Simone
ABSTRACT: Polycyclic Aromatic Hydrocarbons (PAHs) are ubiquitous environmental contaminants and their accurate determination is very important to human health and environment safety. In this review, sorptive-based micro-extraction techniques [such as Solid-Phase Micro-extraction (SPME), Stir Bar Sorptive Extraction (SBSE), Micro-extraction in Packed Sorbent (MEPS)] and solvent-based micro-extraction [Membrane-Mediated Liquid-Phase Micro-extraction (MM-LPME), Dispersive Liquid-Liquid Micro-extraction (DLLME), and Single Drop Micro-extraction (SDME)] developed for quantification of PAHs in environmental, biological and food samples are reviewed. Moreover, recent micro-extraction techniques that have been coupled with other sample extraction strategies are also briefly discussed. The main objectives of these micro-extraction techniques are to perform extraction, pre-concentration and clean up together as one step, and the reduction of the analysis time, cost and solvent following the green chemistry guidelines. Graphical Abstract: uf0001